Delphi consensus survey: the opinions of patients living with refractory ulcerative proctitis and the health care professionals who care for them - Philip Smith; Stuart Bloom; Christian Selinger; Ailsa Hart; Christopher Lamb; Anjan Dhar; Helen Steed; Matthew Brookes; Jonathan Macdonald; Ian Arnott; Shellie Radford; Gordon W Moran; et al. (BMJ Open Gastroenterology)
Background Refractory ulcerative proctitis presents a huge clinical challenge not only for the patients living with this chronic, progressive condition but also for the professionals who care for them. Currently, there is limited research and evidence-based guidance, resulting in many patients living with the symptomatic burden of disease and reduced quality of life. The aim of this study was to establish a consensus on the thoughts and opinions related to refractory proctitis disease burden and best practice for management.Methods A three-round Delphi consensus survey was conducted among patients living with refractory proctitis and the healthcare experts with knowledge on this disease from the UK. A brainstorming stage involving a focus group where the participants came up with an initial list of statements was completed. Following this, there were three rounds of Delphi surveys in which the participants were asked to rank the importance of the statements and provide any additional comments or clarifications. Calculation of mean scores, analysis of comments and revisions were performed to produce a final list of statements.Results In total, 14 statements were suggested by the focus group at the initial brainstorming stage. Following completion of three Delphi survey rounds, all 14 statements reached consensus following appropriate revision.Conclusions We established consensus on the thoughts and opinions related to refractory proctitis from both the experts who manage this disease and the patients living with it. This represents the first step towards developing clinical research data and ultimately the evidence needed for best practice management guidance of this condition.